Model pro určení přirození míry nezaměstnanosti z mezery produktu - Dobrylovský, Jiří (Univerzita Pardubice, 2019)
Since the moment when Milton Friedman introduced a natural rate of unemployment into economic theory, this indicator has been one of the most important quantities in macroeconomics. However, in contrast to other key macroeconomic indicators, the natural rate of unemployment is very difficult to be accurately quantified. The following paper suggests a simple mathematic model, on whose base the natural rate of unemployment can be determined. This model was used to set the natural rate of unemployment in the Czech Republic and its development over time period of the last 23 years based on the Macroeconomic Forecast by the Ministry of Finance of the Czech Republic and compared with Okun´s Law. When calculating the natural rate of unemployment the suggested model eliminates the differences resulting from different utilization of production capacities and the changing rate of economic activity of population in the course of time. As all other models, this model also works with certain simplified assumptions; however, its advantage is the possibility of gradual implementation of more and more difficult parameters of real economy as new variables. Nevertheless, even in its basic form, the model provides good results, which coincide with theoretic basis and monitored facts.
Model for determination of natural rate of unemployment from GDP GAP
Keywords: natural unemployment rate; participation rate; potential product; Okun's law; labor market; C29; E32; J64